Electrode array extrusion through the posterior canal wall presenting as a delayed post-cochlear implant complication. (November 2015) - Rangabashyam, Mahalakshmi; Poh, Sharon Shuxian; Low, Wong Kein
Abstract : Objectives and importance: Cochlear implantation is an established, reliable, and safe procedure with a low complication rate. Electrode array extrusion through the posterior aspect of external ear canal is a potential major complication of cochlear implant surgery that may result in revision surgery or explantation. Although there have been previous case reports of such extrusions through the tympanic membrane, this is the first well-documented report of an extrusion through the posterior canal wall which was previously intact. Clinical presentation: In this case report, we present a case of electrode array extruding through an initially intact posterior canal wall presenting as a delayed post-operative complication in a 13-year old Asian boy. Intervention: With reference to existing relevant literature, the case is discussed focusing on its management, possible contributing factors, and prevention strategies. Conclusion: Excessive thinning of the bony wall should be avoided as it can potentially break down. Abutment on the posterior canal wall by a coiled electrode array in the mastoid cavity exerting undue pressure on the bony wall can further contribute to additional stress. The implant surgeon must be cognizant of mastoid growth patterns in children. Life-long regular follow-up in implanted patients is crucial.